Pengaruh Ratio Keuangan Terhadap Kinerja Keuangan Pada Perusahaan Sub Sektor Makanan - Enda Noviyanti Simorangkir; Trecya Wijaya; Cindi Yosi Olivia Naibaho; Melvi Amelia Putri (Politeknik Ganesha Medan, 2022)
The purpose of this study is to see the effect of financial ratios on financial performance in food sub-sector companies listed on the Indonesia Stock Exchange both partially and simultaneously. Earnings growth is a measure that compares how much increase in income receipts in the current period with earnings in the current period. then. The greater the opportunity to grow the company, the higher the opportunity for the company to increase its profits. Companies that experience an increase in profits can strengthen the relationship between company size and the level of profit earned where companies that experience an increase in profits can have a larger number of assets so that they have more opportunities to generate profits in the future. The profit growth experienced by a company does not always increase every year, sometimes it will decrease in the following year. The population in this study has all the food sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period, as many as 26 companies and the sample with a total of 65 units of analysis. The research method applies multiple linear regression analysis techniques. The result of this research is that liquidity and activity variables partially have no effect on profit growth in food sub-sector companies listed on the Indonesia Stock Exchange. Leverage and profitability variables partially affect profit growth in food sub-sector companies listed on the Indonesia Stock Exchange. The variables of liquidity, leverage, profitability and activity together affect profit growth in food sub-sector companies listed on the Indonesia Stock Exchange.